KARAKTERISTIK KASUS PADA VISUM ET REPERTUM DENGAN DUGAAN KEKERASAN SEKSUAL DI RSUP SANGLAH DENPASAR - I Gde Hary Eka Adyana (Fakultas Kedokteran, Universitas Palangka Raya, 2021)
Sexual abuse is a crime that can be found all over the world, at all levels of society and regardless of age. One of the important components in disclosing cases of sexual abuse is visum et repertum. Visum et repertum (VeR) is a written statement made based on the request of the investigator containing everything seen and found in the examination according to their knowledge as best as possible for the benefit of the judiciary by remembering the oath when accepting responsibilities. Doctors as those who know the human body have a role in making Visum et Repertum (VeR). This study aims to determine the characteristics of request for VeR on suspected sexual abuse cases in Sanglah Hospital, Denpasar based on age, the relationship between victim and doer, by places, by physical examination was found, by hymen condition, and history of previous sexual intercourse. This research is a retrospective descriptive study with the sample were medical record patients who brought requests for visum et repertum with sexual abuse cases at Sanglah Hospital, Denpasar from January 1st 2014 until December 31st 2015. Within a period of 2 years, a request for visum et repertum of suspected sexual abuse to Sanglah Hospital, Denpasar was obtained as many as 113 cases, only 93 cases was included in this study. The mostpercentage of cases by age was 17-25 years old (25.8%), by the relationship between doers was the lover (52,7%), by places was at boarding house (32,3%), by physical examination was found injuries to the genitals only (72.0%), by the hymen had old tears (73.1%), and by most of the victims had have sex before (73.1%).